Circulating Tumour Cells, Circulating Tumour DNA and Circulating Tumour miRNA in Blood Assays in the Different Steps of Colorectal Cancer Management, a Review of the Evidence in 2019. (16th December 2019) - Christou, Niki; Meyer, Jeremy; Popeskou, Sotirios; David, Valentin; Toso, Christian; Buchs, Nicolas; Liot, Emilie; Robert, Joan; Ris, Frederic; Mathonnet, Muriel
Abstract : Despite many advances in the diagnosis and treatment of colorectal cancer (CRC), its incidence and mortality rates continue to make an impact worldwide and in some countries rates are mounting. Over the past decade, liquid biopsies have been the object of fundamental and clinical research with regard to the different steps of CRC patient care such as screening, diagnosis, prognosis, follow-up, and therapeutic response. They are attractive because they are considered to encompass both the cellular and molecular heterogeneity of tumours. They are easily accessible and can be applied to large-scale settings despite the cost. However, liquid biopsies face drawbacks in detection regardless of whether we are testing for circulating tumour cells (CTCs), circulating tumour DNA (ctDNA), or miRNA. This review highlights the different advantages and disadvantages of each type of blood-based biopsy and underlines which specific one may be the most useful and informative for each step of CRC patient care.